Fruit selection of a binturong (Arctictis binturong) by focal animal sampling in Sabah, Malaysian Borneo - Miyabi Nakabayashi; Abdul Hamid Ahmad; Shiro Kohshima (Walter de Gruyter GmbH, 2016)
We investigated fruit selection of a radio-collared female binturong (Arctictis binturong pageli Schwarz, 1911) by focal animal sampling in Sabah, Malaysian Borneo. We recorded seven food species from 12 feeding trees over 16 months. The radio-collared binturong fed only ripe fig fruits (Ficus spp., Moraceae), suggesting that her diet largely depended on figs. As the present study was based on only one female individual, more efforts are needed to elucidate the feeding ecology of this cryptic carnivore.